2016
DOI: 10.1371/journal.pone.0160706
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Poverty in Southern India: A Comparison of Socio-Economic Scales Evaluated against Childhood Stunting

Abstract: IntroductionSocioeconomic status (SES) scales measure poverty, wealth and economic inequality in a population to guide appropriate economic and public health policies. Measurement of poverty and comparison of material deprivation across nations is a challenge. This study compared four SES scales which have been used locally and internationally and evaluated them against childhood stunting, used as an indicator of chronic deprivation, in urban southern India.MethodsA door-to-door survey collected information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…The numbers of children evaluated are small, place of residence was used as indicator of socioeconomic status without specific classification of each household, and there was no objective assessment of the environment or hygiene behavior of each household. However, we have previously assessed the socioeconomic status and household hygiene levels in Chinnallapuram and have found most families classified as low-middle or low-income status by the modified Kuppuswamy scale, 21 whereas all campus residents are of high socioeconomic status by the same scale. Another potential limitation of this study is that the assessment of fecal biomarkers is confined to only fecal calprotectin and MPO, both of which are only indicative of gut inflammation and not intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of children evaluated are small, place of residence was used as indicator of socioeconomic status without specific classification of each household, and there was no objective assessment of the environment or hygiene behavior of each household. However, we have previously assessed the socioeconomic status and household hygiene levels in Chinnallapuram and have found most families classified as low-middle or low-income status by the modified Kuppuswamy scale, 21 whereas all campus residents are of high socioeconomic status by the same scale. Another potential limitation of this study is that the assessment of fecal biomarkers is confined to only fecal calprotectin and MPO, both of which are only indicative of gut inflammation and not intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“… CAP : Chinnallapuram; KASPA: Kaspa; RNP: Ramnaickanpalayam, VSPM: Vasanthapuram # Row percentage * Socio-economic status was classified as low, middle and high using the modified Kuppusamy scale that included education, occupation and selected assets [19]…”
Section: Resultsmentioning
confidence: 99%
“…* Socio-economic status was classified as low, middle and high using the modified Kuppusamy scale that included education, occupation and selected assets [19]…”
Section: Resultsmentioning
confidence: 99%
“…A study by Wang et al reported lower caries prevalence in participants with higher income rate due to more knowledge of caries prevention 5 , whereas Amin et al and Carmichael et al reported no statistically significant association with caries rate. 6 Chandra Shekar B et al reported higher caries prevalence 43.3% in upper economic status than in lower economic status.…”
Section: Discussionmentioning
confidence: 95%